2004
DOI: 10.1007/s00418-004-0687-8
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the cholinergic gene locus in the rat placenta

Abstract: High amounts of acetylcholine (ACh) and its synthesising enzyme choline acetyltransferase (ChAT) have been detected in the placenta. Since the placenta is not innervated by extrinsic or intrinsic cholinergic neurons, placental ACh and ChAT originate from non-neuronal sources. In neurons, cytoplasmic ACh is imported into synaptic vesicles by the vesicular acetylcholine transporter (VAChT), and released through vesicular exocytosis. In view of the coordinate expression of VAChT and ChAT from the "cholinergic gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 33 publications
3
27
0
Order By: Relevance
“…Our results are in accordance with western blot experiments demonstrated by others (Klapproth et al 1997;Pfeil et al 2004). Beside the major protein of 69 kDa in rat placenta, visceral yolk sac epithelium and brain additional ChAT proteins of lower molecular weight were detected in rat brain, visceral yolk sac epithelium, and human bronchial epithelium, respectively (Klapproth et al 1997;Pfeil et al 2004). Taken together, these observations indicate that multiple spliced forms of ChAT may be responsible for the synthesis of ACh observed in the present study.…”
Section: Discussionsupporting
confidence: 81%
“…Our results are in accordance with western blot experiments demonstrated by others (Klapproth et al 1997;Pfeil et al 2004). Beside the major protein of 69 kDa in rat placenta, visceral yolk sac epithelium and brain additional ChAT proteins of lower molecular weight were detected in rat brain, visceral yolk sac epithelium, and human bronchial epithelium, respectively (Klapproth et al 1997;Pfeil et al 2004). Taken together, these observations indicate that multiple spliced forms of ChAT may be responsible for the synthesis of ACh observed in the present study.…”
Section: Discussionsupporting
confidence: 81%
“…Previous studies from our laboratory and other laboratories have shown that acetylcholine and M3 receptors are expressed in a wide variety of normal endothelial and epithelial cell types (5)(6)(7)(8)(9)(10)(11)(12)(13). This suggests that cancers derived from these diverse cell types will similarly coexpress acetylcholine and M3 receptors.…”
Section: Resultsmentioning
confidence: 71%
“…Recently, it has been established that acetylcholine is also widely synthesized by a variety of nonneuronal cell types, including keratinocytes (5), airway epithelial cells (6,7), glia (8), vascular endothelium (9, 10), placental trophoblasts (11), and ovarian follicular cells (12) among others (13). Expression of acetylcholine has been unambiguously shown in these cells and tissues as shown by the presence of choline acetyltransferase, the enzyme that synthesizes acetylcholine, and by demonstration of acetylcholine synthesis in these cells as measured by high-performance liquid chromatography (HPLC).…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we present data suggesting that Re and Rd out of five representative ginsenosides isolated from ginseng deserve to be developed as new promising candidates for enhancement of cognition via increasing ChAT/VAChT expression, and thereby elevating ACh in the N2a neuroblastoma cell model. As cholinergic neurons are known to coexpress ChAT and VAChT proteins, 23) MAP-2, a neuronal differentiation marker, was also included in this study. 24) N2a cells were treated with or without K252a (50 nM) in the presence of Re (5 碌g/mL) or Rd (5 碌g/mL) for 48 h. Total RNA and protein lysates were isolated as described in Materials and Methods for analysis of protein (A) and mRNA (B-D) expression under the same conditions.…”
Section: Discussionmentioning
confidence: 99%